PENGEMBANGAN KETRAMPILAN MENJAHIT PARA PENYANDANG DISABILITAS KABUPATEN GROBOGAN BERSAMA LPK BELVA - Wahyuningsih, Susanti; Tasriastuti, Nurrohmi Ambar; Kurniawati, Endang; Sulikah, Sulikah; Fitriani, Fatma Awalia; Pratiwi, Yusi; Iffah, Milchatul; Sidiq, Fajar (Fokus ABDIMAS, 2023)
Development of sewing skills for persons with disabilities is carried out with the aim of improving their skills so that they can open jobs or business. This sewing training development activity is in the form of training in making product designs and making dress patterns. The results in this study are that person with disabilities who are considerate incapable of being productive, creative and innovative by being given sewing development training are able to help improve their business skills which can be useful for starting a business.Keywords : Development, disabilities, training, sewing skills